Effect of Training and Career Development on Motivation and Employee Performance - Aditya, I Putu Khrisna Raka; Pio, Riane Johnly; Rumawas, Wehelmina (International Journal of Science and Society, 2024)
This research aims to determine and analyze the influence of Training and Career Development on Employee Motivation and Performance at Airnav Indonesia Manado Branch Office. This study uses a quantitative approach. The population in this study were all functional employees of AirNav Indonesia Manado Branch Office. The data collection technique is by distributing questionnaires, while secondary data is collected through literature study after reading various literature. The data analysis technique uses the Partial Least Square Structural Equation Model (PLS-SEM) method with the help of SmartPLS software version 4. The findings of this study reveal that Training and Career Development has a positive and significant effect on motivation. Training and Motivation has a positive and significant effect on employee performance, whereas Career Development has no effect on Employee Performance. Meanwhile Motivation can mediates the effect of training and career development on employee performance.